Pregnancy Induces an Earlier Chronotype in Both Mice and Women. Issue 3 (June 2019) - Martin-Fairey, Carmel A.; Zhao, Peinan; Wan, Leping; Roenneberg, Till; Fay, Justin; Ma, Xiaofeng; McCarthy, Ronald; Jungheim, Emily S.; England, Sarah K.; Herzog, Erik D.
Daily rhythms generated by endogenous circadian mechanisms and synchronized to the light-dark cycle have been implicated in the timing of birth in a wide variety of species. Although chronodisruption (e.g., shift work or clock gene mutations) is associated with poor reproductive outcomes, little is known about circadian timing during pregnancy. This study tested whether daily rhythms change during full-term pregnancies in mice and women. We compared running wheel activity continuously in both nonpregnant ( n = 14) and pregnant ( n = 13) 12- to 24-week-old C57BL/6NJ mice. We also monitored wrist actigraphy in women ( N = 39) for 2 weeks before conception and then throughout pregnancy and measured daily times of sleep onset. We found that on the third day of pregnancy, mice shift their activity to an earlier time compared with nonpregnant dams. Their time of daily activity onset was maximally advanced by almost 4 h around day 7 of pregnancy and then shifted back to the nonpregnant state approximately 1 week before delivery. Mice also showed reduced levels of locomotor activity during their last week of pregnancy. Similarly, in women, the timing of sleep onset was earlier during the first and second trimesters (gestational weeks 4-13 and 14-27) than before pregnancy and returned to the prepregnant state during the third trimester (weeks 28 until delivery). Women also showed reduced levels of locomotor activity throughout pregnancy. These results indicate that pregnancy induces changes in daily rhythms, altering both time of onset and amount of activity. These changes are conserved between mice and women.